EARLY MEDIEVAL CULTURE OF THE SETTLED PEASANT POPULATION OF THE MIDDLE SYRDARYA (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This article examines the early medieval culture of the settled peasant population in the Middle Syrdarya region, focusing on the period between the 6th and 13th centuries. It explores the social, economic, and cultural aspects of life in this area, emphasizing how local communities adapted to their environment and interacted with broader regional influences. Key topics include agricultural practices, settlement patterns, and material culture, including pottery and tools. The study also highlights the role of trade and external contacts in shaping local cultural developments. Through a detailed analysis of archaeological findings and historical records, the article provides insights into the daily lives of these early medieval peasants and their contributions to the region's historical and cultural heritage.